STUDI TENTANG PERSEPSI MAHASISWA TERHADAP IMPLEMENTASI UU NO. 19 TAHUN 2016 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK DI UNIVERSITAS RIAU - Yaumi Fitriyani; Hambali Hambali; Jumili Arianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated by advances in the field of Information and Communication Technology that have a big impact in people's social lives, this progress can have a positive impact and also a negative impact. Therefore, in anticipation of this, the Government of Indonesia issued UU No. 11 of 2008 on Information and Electronic Transactions, which was later revised to UU No. 19 of 2016 on Information and Electronic Transactions. The problem formulation in this study is how students of Riau University perceive the Implementation of Chapter VII of UU No. 19 of 2016 on Information and Electronic Transactions. This study aims to find out the Perception of Riau University Students towards the Implementation of Chapter VII of UU No. 19 of 2016 on Information and Electronic Transactions. The benefits of research results are in terms of science development, being a donation or reference material (relevant) in conducting further research and can be a learning for all parties, especially students who conduct Research on UU No. 19 of 2016. This research method is Descriptive Quantitative, data collection instrument used in this research is questionnaire and interview consisting of 10 indicators with 30 questions. The data is taken with the slovin formulation n = N (1 + Ne2). The population in this study was students of Riau University. Samples in this study were taken using purposive sampling techniques. Based on the results of the study found that the average percentage value of alternative answers of dominant respondents is 51% where this range is in the category of "Quite Good" with the presence in the range of 50.01 - 75%. Thus the Perception of Students perception of Riau University towards the implementation of Chapter VII of UU No. 19 of 2016 on Information and Electronic Transactions is Quite Good.Key Words: Perception, Students, UU No. 19 of 2016